2017
DOI: 10.5152/tpd.2016.4869
|View full text |Cite
|
Sign up to set email alerts
|

Demodex spp. Infestation Associated with Treatment-Resistant Chalazia and Folliculitis

Abstract: ÖZDemodikozis demodex akarları ile gelişen pilosebase ünitenin ektoparazitidir. Demodikozis primer bir deri hastalığı olabileceği gibi folikülit, rozasea gibi inflamatuar dermatozlara sekonder olarak da görülebilir. Demodex blefariti yaygın görülen enfeksiyöz göz hastalığıdır, ancak sıklıkla ihmal edilir. Bu akarlar lipaz enzimleri içerir ve yüzeylerinde bakteri taşırlar. Demodex spp. enfestasyonu giderek artan bir şekilde halk sağlığı sorunu haline gelmiştir. 29 yaşında erkek hasta dermatoloji polikliniğine 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Our current results challenge these approaches. The anti-demodex therapy was emphasized by some previous studies ( Cheng et al, 2015 ; Akcinar et al, 2016 ). Therefore, apart from the application of antibacterial agents, a combination of anti-demodex therapy to reduce demodex count should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current results challenge these approaches. The anti-demodex therapy was emphasized by some previous studies ( Cheng et al, 2015 ; Akcinar et al, 2016 ). Therefore, apart from the application of antibacterial agents, a combination of anti-demodex therapy to reduce demodex count should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, D. folliculorum was supposed to cause chronic anterior blepharitis, while D. brevis has been considered to cause posterior blepharitis ( Cheng et al, 2015 ). Meanwhile, there have been some studies that have suggested that metronidazole and tea tree oil are effective choices for the treatment of demodex infestation in blepharitis ( Cheng et al, 2015 ; Akcinar et al, 2016 ). However, most people who have these obligate mites are healthy and there is no rigorous evidence demonstrating that Demodex mite infestation promotes bacterial infection in blepharitis ( Clifford and Fulk, 1990 ; Bezza Benkaouha et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These mites are transmitted through close person-to-person contact, but the pathogenic mechanism is not fully understood [ 3 ]. D. folliculorum and D. brevis are more often found in the eyelashes and ears, and may also be found in other sites, especially in the forehead and nose region [ 2 , 4 – 7 ]. Although many recent studies suggest that these parasites play a role in the etiopathogenesis of disorders such as skin diseases and facial blepharitis, others regard the presence of mites in the pilosebaceous follicles as harmless [ 8 ].…”
Section: Introductionmentioning
confidence: 99%